2017
DOI: 10.1177/1077559517733815
|View full text |Cite
|
Sign up to set email alerts
|

The “Good Old Days” of Courtroom Questioning: Changes in the Format of Child Cross-Examination Questions Over 60 Years

Abstract: Recent decades have seen an explosion of research into children's eyewitness capabilities and resulted in legal reform to render the adversarial trial process more child friendly. Many, however, have been left with the feeling that the most intimidating legal process for child complainants-cross-examination-has not changed meaningfully despite its potential to distort children's evidence. To test this possibility, we compared the cross-examination questioning of Australian child sexual abuse complainants in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
0
11
1
1
Order By: Relevance
“…Hanna et al () not only found that defense lawyers used more double negatives and questions with two or more subordinate clauses than prosecutors but they also found that prosecutors asked more questions containing passive voice than defense lawyers. Hanna et al (), Andrews and Lamb (), and Zajac et al () all showed that defense lawyers did not make accommodations for children's age whereas Zajac et al () reported that younger children were asked less complex questions than older children.…”
Section: Question Complexity In Courtroomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hanna et al () not only found that defense lawyers used more double negatives and questions with two or more subordinate clauses than prosecutors but they also found that prosecutors asked more questions containing passive voice than defense lawyers. Hanna et al (), Andrews and Lamb (), and Zajac et al () all showed that defense lawyers did not make accommodations for children's age whereas Zajac et al () reported that younger children were asked less complex questions than older children.…”
Section: Question Complexity In Courtroomsmentioning
confidence: 99%
“…Despite this, child witnesses are commonly subjected to developmentally inappropriate questioning in and out of court that adversely affects the richness and accuracy of their responses (Andrews & Lamb, ; Carter, Bottoms, & Levine, ; Hanna, Davies, Crothers, & Henderson, ; Lamb et al, ; Zajac & Hayne, ). Not only are children frequently asked risky close‐ended and suggestive questions (Andrews & Lamb, ; Zajac, Westera, & Kaladelfos, ; see Table for definitions) that have been found to contaminate the information provided (Lamb, Orbach, Hershkowitz, Esplin, et al, ) and elicit self‐contradictions (Andrews & Lamb, ) but they are often also asked questions whose complexity exceeds their developmental capabilities (Andrews & Lamb, ; Hanna et al, ; Zajac, Gross, & Hayne, ). Accordingly, British lawyers have been instructed to adapt their questions to children's developmental abilities (Criminal Practice Directions, ) but when children are asked complex, close‐ended, and suggestive questions, they are unable to give their best evidence in court.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the frequency of delayed disclosure in CSA cases, lack of medical evidence to corroborate a child’s claims, and concerns about child suggestibility, enormous weight is then placed on the child’s report if the case reaches trial (Goodman & Bottoms, 1993). While other countries have adapted the testifying process to accommodate the unique needs of children (Pipe & Henaghan, 1996; Westcott, Davies, & Spencer, 1999; Zajac, Westera, & Kaladelfos, 2018), the United States has not. For example, New Zealand has reformed the testifying process for children, allowing them to testify via closed-circuit television (Hanna, Davies, Crothers, & Henderson, 2012).…”
mentioning
confidence: 99%
“…Little prior research has considered the degree to which lawyers tailor their questions to the developmental needs of the complainant. An Australian study analyzed sexual assault trial transcripts involving child complainants aged 6–17 years, revealing that defense lawyers exhibited some sensitivity to the age of the complainant in their questioning (Zajac et al, 2018). Defense asked younger children a higher proportion of cued-recall questions and a lower proportion of leading questions compared to older children.…”
Section: Do Lawyers Adapt Their Questioning Style To the Complainant’s Developmental Stage?mentioning
confidence: 99%
“…Few studies have examined this question, and the findings that do exist are mixed. There is some evidence that younger children are asked fewer questions during cross-examination than older children (Zajac & Cannan, 2009), however, cross-examination even with young children is typically lengthy (the duration of cross-examination in Australian child sexual assault trials is much longer for all witnesses than it was a few decades ago; Zajac et al, 2018).…”
Section: Do Lawyers Adapt Their Questioning Style To the Complainant’s Developmental Stage?mentioning
confidence: 99%